README [Test Matrix & Description - ERICE] - Vincent, Abhay; Pervier, Marie Laure A.; Pervier, Hugo (Cranfield University, 2023)
The item consists of a presentation ('pptx' format) which describes the two distinct test matrix conditions for the ERICE tests and a text file which describes the process of all the various tests performed within this research work. These conditions were used for all the testing done within the ERICE project.
Keywords: test matrix; Ice Adhesion Strength; ice protection; Air cycle machine